2x-3(-5x-2)=91

Simple and best practice solution for 2x-3(-5x-2)=91 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-3(-5x-2)=91 equation:


Simplifying
2x + -3(-5x + -2) = 91

Reorder the terms:
2x + -3(-2 + -5x) = 91
2x + (-2 * -3 + -5x * -3) = 91
2x + (6 + 15x) = 91

Reorder the terms:
6 + 2x + 15x = 91

Combine like terms: 2x + 15x = 17x
6 + 17x = 91

Solving
6 + 17x = 91

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6' to each side of the equation.
6 + -6 + 17x = 91 + -6

Combine like terms: 6 + -6 = 0
0 + 17x = 91 + -6
17x = 91 + -6

Combine like terms: 91 + -6 = 85
17x = 85

Divide each side by '17'.
x = 5

Simplifying
x = 5

See similar equations:

| 175m-75m+57000=60300-200m | | 16=2(x+4) | | 1.29x=11.61 | | 50+31= | | 8t^3-6t+1=0 | | 7(5a-4)-1=14-a | | -7(6x-9)-7(-9x-9)= | | 2x+1+30=180 | | -6.4(x-1.5)=12.8 | | 90=5x+25 | | 2s+4=5(14-2s) | | 12000*.0127= | | -15+-r=30 | | -10(-3h-2)-10(-2h-9)= | | -8.4(x-2.75)=25.2 | | -6(4-8s)=20 | | 6.4x-3.5=52.2 | | F+v-e=2fore | | 1.6=-0.3 | | 7y+4x-2=0 | | .073x+.0127(12000-x)=1308 | | 25500+2000=47900-800 | | 9=0+0 | | 34+a=62 | | -3x-1=-10x-8 | | 4xy^4z^3-4xy^4z^3= | | M-56=10 | | 12x-8=-308 | | -5(t-3)-(t+1)=3 | | 7k+10-15-4K=-13 | | h+14=33 | | 9x-6=4x+1 |

Equations solver categories